The Tilt-Quadrotor: modelling and attitude stabilization - Marques, R.; Moutinho, A.; Cunha, F. (My University, 2018)
This paper presents the study on a new type of aircraft, the Tilt-Quadrotor. This multirotor platform differs from classical quadrotors by having four servo motors that tilt two of its four rotors, in two different directions each, allowing the horizontal motion to be executed without tilting the platform. The derived Tilt-Quadrotor model is explained and implemented in a simulator. LQR controllers are designed for attitude and altitude stabilization, and validated in simulation. An approach based on the linearized model is implemented experimentally in a PixHawk autopilot, achieving the stabilization of all three attitude angles of a Tilt-Quadrotor prototype.